2021
DOI: 10.3390/nano11112858
|View full text |Cite
|
Sign up to set email alerts
|

A Multifunctional Polymeric Micelle for Targeted Delivery of Paclitaxel by the Inhibition of the P-Glycoprotein Transporters

Abstract: P-glycoprotein (P-gP) efflux-mediated multidrug resistance is a fundamental aspect of chemotherapeutic failure in oncology. The current study aims to deliver paclitaxel (PTX) specifically at the target site with improved in vivo efficacy of poorly permeable PTX against solid tumors. Multifunctional polymeric micelles as targeted delivery have been devised for loading and release of PTX. Mucoadhesion, permeation enhancement, oral pharmacokinetics, biodistribution, and toxicological studies were carried out to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…Efiana et al [ 234 ] modified self-emulsifying drug delivery systems (SEDDS) with 0.5% papain-palmitate and found a threefold increase in mucus permeability when compared to unmodified SEDDS. Razzaq et al [ 235 ] synthesized papain-functionalized thiolated redox multifunctional polymeric micelles for delivery of paclitaxel to solid tumors and demonstrated a 7.89-fold improvement in mucus penetration when compared to pure paclitaxel.…”
Section: Active Mucus-penetrating Systems: Mucolysismentioning
confidence: 99%
“…Efiana et al [ 234 ] modified self-emulsifying drug delivery systems (SEDDS) with 0.5% papain-palmitate and found a threefold increase in mucus permeability when compared to unmodified SEDDS. Razzaq et al [ 235 ] synthesized papain-functionalized thiolated redox multifunctional polymeric micelles for delivery of paclitaxel to solid tumors and demonstrated a 7.89-fold improvement in mucus penetration when compared to pure paclitaxel.…”
Section: Active Mucus-penetrating Systems: Mucolysismentioning
confidence: 99%
“…Based on the affinity of the transporter protein, the toxicity of the protein to the normal cells, and the side effects, the modulators are selected. Anticancer drugs are administered along with the inhibitors so that the transporter proteins are kept occupied and the drug is allowed to accumulate in the cancer cells at an effective lethal concentration, as the inhibitors, when considered on a chemical basis, cause intrinsic toxicity or produce undesired effects [ 44 ]. Recent research supports the use of natural products as MDR modulators.…”
Section: Mdr Modulators and The Mechanisms Of Inhibitorsmentioning
confidence: 99%
“…P-glycoprotein (P-gp) is an efflux transporter, The efflux of diffused intracellular anticancer medicines is mostly caused by overexpression of P-gp in tumour cells, resulting in low bioavailability of the drug. Razzaq, S et al developed a mucopermeating papain functionalized thiolated redox micelle for site-specific administration of paclitaxel, that the developed formulations can inhibit P-gp efflux pump, improve oral bioavailability, higher penetration and enhanced efficacy compared to conventional paclitaxel formulation [ 61 ]. The different types of polymeric micelle for cancer therapy used in clinical trials are shown in Table 3 .…”
Section: Nanocarriers Used In Cancer Therapymentioning
confidence: 99%